“If you work alone on this project, you can’t reach your target”: unpacking the leader’s role in well-performing teams in a maternal and neonatal quality improvement programme in South Africa, before and during COVID-19 - Willem Odendaal; Terusha Chetty; Mark Tomlinson; Ameena Goga; Yages Singh; Shuaib Kauchali; Carol Marshall; Xanthe Hunt (BMC Health Services Research, 2023)
Abstract The South African National Department of Health developed a quality improvement (QI) programme to reduce maternal and neonatal mortality and still births. The programme was implemented between 2018 and 2022 in 21 purposively selected public health facilities. We conducted a process evaluation to describe the characteristics and skills of the QI team leaders of well-performing teams. The evaluation was conducted in 15 of the 21 facilities. Facilities were purposively selected and comprised semi-structured interviews with leaders at three time points; reviewing of QI documentation; and 37 intermittently conducted semi-structured interviews with the QI advisors, being QI technical experts who supported the teams. These interviews focused on participants’ experiences and perceptions of how the teams performed, and performance barriers and enablers. Thematic data analysis was conducted using Atlas.ti. Variation in team performance was associated with leaders’ attributes and skills. However, the COVID-19 pandemic also affected team functioning. Well-performing teams had leaders who effectively navigated COVID-19 and other challenges, who embraced QI and had sound QI skills. These leaders cultivated trust by taking responsibility for failures, correcting members’ mistakes in encouraging ways, and setting high standards of care. Moreover, they promoted programme ownership among members by delegating tasks. Given the critical role leaders play in team performance and thus in the outcomes of QI programmes, efforts should focus on leader selection, training, and support.